[tex]\displaystyle\bf\\f(x)=x^{3} \\\\(-1 \ ; \ 12) \ \ \ \Rightarrow \ \ \ x=-1 \ \ ; \ \ F(x)=12\\\\\\F(x)=\frac{x^{4} }{4} +C\\\\\\12=\frac{(-1)^{4} }{4} +C\\\\\\12=\frac{1}{4} +C\\\\\\C=12-\frac{1}{4} =11\frac{3}{4} =11,75\\\\\\Otvet \ : \ F(x)=\frac{x^{4} }{4} +11,75[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
[tex]\displaystyle\bf\\f(x)=x^{3} \\\\(-1 \ ; \ 12) \ \ \ \Rightarrow \ \ \ x=-1 \ \ ; \ \ F(x)=12\\\\\\F(x)=\frac{x^{4} }{4} +C\\\\\\12=\frac{(-1)^{4} }{4} +C\\\\\\12=\frac{1}{4} +C\\\\\\C=12-\frac{1}{4} =11\frac{3}{4} =11,75\\\\\\Otvet \ : \ F(x)=\frac{x^{4} }{4} +11,75[/tex]